Answer:
a. 20 b. 1 13/16 c. 78 3/4 d. undefined
Explanation:
since f(x)=4x+1 and g(x)=3x/4
a) (f+g)(4)
= f(4) + g(4)
f(4) = 4(4)+1 = 17
g(4) = 3(4)/4 = 3
therefore
(f+g)(4) = 17 + 3 = 20
b) (f-g)(1/4)
= f(1/4) - g(1/4)
f(1/4) = 4(1/4)+1 = 2
g(1/4) = 3(1/4)/4 = 3/16
therefore
(f-g)(1/4) = 2 - 3/16 = 29/16 = 1 13/16
c) (fg)(5)
= f(5) x g(5)
f(5) = 4(5)+1 = 21
g(5) = 3(5)/4 = 15/4
therefore
(fg)(5) = 21 x 15/4 = 315/4 = 78 3/4
d) (f/g)(0)
= f(0) / g(0)
f(0) = 4(0)+1 = 1
g(0) = 3(0)/4 = 0
therefore
(f/g)(0) = 1 / 0 = undefined